Immune-responsive gene 1: The mitochondrial key to Th17 cell pathogenicity in CNS autoimmunity - Mohammad Nematullah; Mena Fatma; Guoli Zhou; Bharat Prajapati; Faraz Rashid; Kameshwar Ayasolla; Mohammad Ejaz Ahmed; Ruicong She; Sajad Mir; Insha Zahoor; Nasrul Hoda; Ramandeep Rattan; et al. (Proceedings of the National Academy of Sciences, 2025)
Pathogenic Th17 cells play crucial roles in CNS autoimmune diseases such as multiple sclerosis (MS), but their regulation by endogenous mechanisms remains unknown. Through RNA-seq analysis of primary brain glial cells, we identified immune-responsive gene 1 ( Irg1 ) as one of the highly upregulated genes under inflammatory conditions. Validation in the spinal cords of animals with experimental autoimmune encephalomyelitis (EAE), a preclinical MS model, confirmed elevated Irg1 levels in myeloid, CD4, and B cells in the EAE group, raising concerns as to whether Irg1 is detrimental or protective. Irg1 knockout (KO) mice exhibited severe EAE disease, increased mononuclear cell infiltration, and increased levels of triple-positive CD4+ T cells expressing IL17a, GM-CSF, and IFNγ. Adoptive transfer in Rag-1 KO and single-cell RNA sequencing highlighted the crucial role of Irg1 in shaping pathogenic Th17 cells. A lack of Irg1 in macrophages elevates Class II expression, promoting the polarization of myelin-primed CD4+ T cells into pathogenic Th17 cells via the NLRP3/IL-1β axis. Moreover, bone marrow chimeras revealed that immune cells lacking Irg1 maintained pathogenic and inflammatory phenotypes, suggesting its protective role in autoimmune diseases, including MS.